The UNIDROIT Principles 2004 the restatement of the lex mercatoria in the new millennium - Hink, Knut Michael (Department of Commercial Law, 2023)
This work tries to examine if somethink like a modern lex mercatoria exists, what if it exists is generally understood as the modern lex mercatoria and to answer the question if the UNIDROIT Principles of International Commercial Contracts (UPICC) are an up to date restatement of this lex mercatoria. For this purpose a description of the roots of the lex mercatoria is given and a survey of the modern development. For the achievment of a satisfying result an overview of the international institutions, organisations and projects and their work in the field of the international and transnational commercial law is presented. The main attention hereby is given to the International Institute for the Unification of private law (UNIDROIT) and CENTRAL. The different understanding and interpretation of the lex mercatoria is analysed and the different approach to the preparation of lists of principles for the international commercial law is surveyed. After a brief summery of the common principles a comparison of different solutions offered by the UPICC and the list of principles published by CENTRAL, other lists of principles, international conventions and national regulations for selected legal problems of importance in the field of the international commercial law is made. The comparison shall give the answer if the UPICC that were first published in 1994 and as an enlarged 2nd edition with only a few revisions in 2004, are still the up to date restatement of the lex mercatoria in the year 2005.